IMPLEMENTASI ALGORITMA DIJKSTRA PADA APLIKASI WISATA KUNINGAN BERBASIS ANDROID - Elda Candra Galih; Rio Andriyat Krisdiawan (NUANSA INFORMATIKA, 2018)
Kuningan Regency is one of the tourist destinations that is quite popular among tourists. Kuningan has many potential tourism object whether it is natural tourism, history, jiarah, and artificial. To find tourism destinations, tourists are usually looking at search engine applications or tourist maps so it takes a long time. To facilitate tourists in finding tourist destinations, it needs an application. The application that will be developed based on preliminary research held at Dinas Pemuda Olahraga dan Pariwisata Kabupaten Kuningan. Mobile-based application is needed in finding the location of tourissm objects and it provides descriptions of attractions, and facilities that exist in the tourism object. It is created only to show the location of existing tourism object in Kuningan Regency. In finding the closest route, it will be displayed in the form of maps. Tourists can choose the location of tourist attractions and initial location of tourists, then the system will display the results of the existing route on the maps. And in this application is also available services to find the location of tourists using GPS technology. And the author uses Dijkstra algorithm to determine the shortest route in finding the route from the initial location to the desired location of the object of tourism. And in the data storage in this application, the author uses MySQL or Apache as a web server in storing data objects and data node,, destination and route concerned with searching the location of the tourist attraction. And on the development of this application he uses client server. Keywords: Dijkstra Algorithma, Nearest Order, Mobile-based Application, Kuningan District, Tourism Object.